Multifaceted death receptor 3 signaling—promoting survival and triggering death. Issue 17 (20th July 2017) - Bittner, Sebastian; Ehrenschwender, Martin
Abstract : Death Receptor 3 (DR3) and its cognate ligand TL1A belong to the tumor necrosis factor superfamily (TNFSF). This sophisticated network of receptor–ligand systems controls innumerable biological processes. For many (if not all) TNFSF ligands and receptors, a role in conditions such as inflammation, tissue development, proliferation, and cell death has been firmly established. However, relatively little is known about DR3 and TL1A. Here, we review novel aspects of DR3 signaling and DR3‐associated signaling pathways before summarizing the function of DR3 in the immune system. The emerging role of DR3 in disease will be addressed before we finally critically discuss the potential therapeutic exploitation of this receptor–ligand pair. Abstract :